The Chamber Musician in the Twenty-First Century - Dogantan-Dack, Mine (MDPI Books, 2022)
In recent research, there has been growing emphasis on the collaborative, social, and collective nature of musical behaviour and practices. Among the emerging hypotheses in this connection are the idea that listening to music is always listening together and being with the other; that music making is a matter of intercorporeality, mutuality, and emphatic attunement; and that creative agency in musical practices is fundamentally a distributed phenomenon. Chamber music provides an ideal context for the testing and actualization of these notions. This Special Issue on chamber music and the chamber musician aims to explore the psychological, social, cultural, historical, and artistic issues in the practice of classical chamber music in the twenty-first century. Contributions are invited on any of these aspects and issues involved in being a contemporary classical chamber musician. Authors are encouraged to contextualise their research by reference to the recent literature on collaborative musicking, and among the topics they may choose to address are the cultural and musical demands chamber musicians face and the implications of these demands for their artistic practice, the ways the twenty-first-century chamber musicians engage with historical practices, the newly emerging musical identities and artistic roles available to them, and expressivity in current chamber music practices.